Intrinsic rewards experienced by a group of dentists working with underserved populations. (21st July 2014) - Gardner, SP; Roberts‐Thomson, KF; Winning, TA; Peterson, R
Abstract Background The aim of this study was to explore, using qualitative methods, the intrinsic reasons why dentists work with underserved groups. Minority and marginalized groups of Australians suffer a greater burden of dental disease than the general population due to disparities in accessing care. Recruitment and retention of dentists to care for underserved groups is problematic due to personal, professional and structural reasons. What drives dentists to work with underserved groups is not widely known. Methods Sixteen dentists were recruited using 'snowball' purposeful sampling. Semi‐structured in‐depth interviews were conducted. Thematic analysis was conducted on the transcriptions to identify themes. Results Five key themes emerged: (1) 'tapped on the shoulder', being personally approached or invited; (2) 'dental school experience', the challenges faced as a student; (3) 'empathic concern', the non‐judgemental expressions of care toward others; (4) 'resilience', the ability to bounce back after setbacks; (5) 'intrinsic reward', the personal gain and satisfaction received. This study focuses on the intrinsic rewards which were found to be simple, unexpected, and associated with relieving pain, community engagement and making a difference. Conclusions Emphasizing personal fulfilment and intrinsic reward could be useful when promoting dentistry as a career and when encouraging graduates to consider working with disadvantaged groups.